EFEKTIVITAS PELAKASANAAN PEMBERDAYAAN PEREMPUAN UNTUK MENINGKATKAN PRODUKTIFITAS JANDA - Suganda, Silviani; Cisyara, Sinta Naila; Andini, Sri; Nuraeni, Synta; Nurazizah, Yani; Nurlaila, Nurlaila (CV Bayfa Cendekia Indonesia Bekerjasama dengan Jurusan/Program Studi Pendidikan Masyarakat FKIP Universitas Siliwangi, 2024)
The empowerment of women in enhancing economic participation and self-reliance aims to actively engage women in economic activities, improve their access to resources, and business opportunities. Focusing on enhancing skills and understanding of digital marketing, this empowerment initiative is expected to create a positive impact on the overall economic growth and autonomy of women in Pasirbatang Village. This endeavor is based on issues highlighted by the Village Head, indicating that some widows in Pasirbatang Village are less productive due to unemployment, facing difficulties in meeting their basic needs. The implemented steps include observation, socialization, counseling, and training, including hands-on processing of Sacha Inchi beans. Empowering women by utilizing local resources in Pasirbatang Village aims to enhance their economic and social autonomy. The outcomes of the women empowerment program in Pasirbatang Village are part of the Ecotourism initiative to boost the community's economy. One unique aspect of Pasirbatang Village is the Sacha Inchi beans, which have numerous benefits but have not been fully utilized in high-value processed products. Sacha Inchi plants cultivated around the proposed tourist area are a rare find in several locations. The identified potentials can be collaboratively harnessed to achieve empowerment goals. The women empowerment program in Pasirbatang Village has progressed smoothly, marked by increased motivation and creativity among widows utilizing local resources, such as Sacha Inchi beans. Community empowerment is carried out participatively, involving the village community in the planning, implementation, and evaluation of development initiatives.